(untitled) (Bridging Cultures, 2023)
English folk music motifs have been passed down through generations and they can still be found in current songs. However, they are less likely to be found in the lyrics of artists who are as popular as Taylor Swift. What is more, folklore is an album that is markedly different from her previous productions in this approach to alternative/indie music. Those folk music motifs that are studied in this paper are the narration of stories from multiple points of view and their narrators; the type of language used in the lyrics, which is closely related to historical nostalgia and the search for a return to nature; and the performance of a particular aesthetic known as “cottagecore”. The influence of a distinct production frame given social distancing during the Covid-19 pandemic is critical to explain the drastic change in the artist’s lyrics and aesthetic in this production and how the album came to be promoted. In this way, different narrative and performative aspects account for the transmission of a palpable wish to transcend the contemporary and reach a legacy state for future generations.